Plating of Metacarpal Fractures with Locked or Nonlocked Screws, a Biomechanical Study: How Many Cortices are Really Necessary?. (December 2013) - Barr, Cameron; Behn, Anthony W; Yao, Jeffrey
Background: Dorsal plate and screw fixation is a popular choice for metacarpal stabilization. The balance between construct stability and soft tissue dissection remains a surgical dilemma. Historically, six cortices of bone fixation on either side of a fracture were deemed necessary. This study aims to elucidate whether four cortices of locked fixation on either side of the fracture is equivalent to the current gold standard of six cortices of nonlocked fixation on either side of the fracture. If so, less dissection to insert shorter plates with fewer screws could be used to stably fix these fractures. Methods: With biomechanical testing-grade composite Sawbones, a comminuted metacarpal fracture model was used to test two fixation constructs consisting of a standard dorsal plate and either six bicortical nonlocking screws (three screws per segment) or four bicortical locking screws (two screws per segment). Thirty specimens were tested to failure in cantilever bending and torsion. Results: There was statistical equivalence between the locking and nonlocking constructs in cantilever bending stiffness, torsional stiffness, maximum bending load, and maximum torque. Conclusion: The tested metacarpal fracture model had equivalent biomechanical properties when fixed with a standard dorsal plate and either six bicortical nonlocking screws or four bicortical locking screws. By utilizing fewer cortices of fixation, there will be less dissection and less soft tissue stripping during fixation of metacarpal fractures. This will also be of benefit in very proximal or distal fractures as multiple cortices of fixation are often difficult to obtain during stabilization of these challenging fractures.